Modification of oligonucleotides with weak basic residues via the 2′-O-carbamoylethyl linker for improving nuclease resistance without loss of duplex stability and antisense activity. Issue 19 (29th April 2019) - Masaki, Yoshiaki; Yamamoto, Keishi; Yoshida, Keita; Maruyama, Atsuya; Tomori, Takahito; Iriyama, Yusuke; Nakajima, Hiroyuki; Kanaki, Tatsuro; Seio, Kohji
Abstract : For the improvement of nuclease resistance, four kinds of new modifications through a carbamoylethyl linker were designed. Abstract : For the improvement of nuclease resistance, four kinds of new modifications through a carbamoylethyl linker were designed. Among them, the 2′- O -[2- N -{2-(benzimidazol-1-yl)ethyl}carbamoylethyl] modification showed 20-fold longer half-life when treated with a 3′ to 5′ exonuclease compared to the 2′- O -methoxyethyl (MOE) modification, which is used in approved drugs. In addition, this large modification did not disturb the binding affinity or RNase H-dependent antisense activity. From these findings, it could be concluded that an adequate linker, such as carbamoylethyl in this study, could extend the utility of 2′- O -modification without loss of the properties of nucleic acids. This strategy would be useful for the development of nucleic acid therapeutics.